2019
DOI: 10.3390/en12234409
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Evidence for Weather Regimes Governing Solar Power Generation in Kuwait

Abstract: With electricity representing around 20% of the global energy demand, and increasing support for renewable sources of electricity, there is also an escalating need to improve solar forecasts to support power management. While considerable research has been directed to statistical methods to improve solar power forecasting, few have employed finite mixture distributions. A statistically-objective classification of the overall sky condition may lead to improved forecasts. Combining information from the synoptic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…An important condition for this is to find the law of distribution of random variables, the choice of a mathematical model with a minimum number of parameters, the empirical distribution of the test characteristic in satisfactory certain physical and geographical conditions and within the required accuracy. Modeling the regime of geophysical processes makes it possible to determine the variability of the energy properties of solar radiation or water flow, the integral distribution function and the integral provision of the initial value [18]. It is necessary for further research to fully ensure the intensity of research characteristics, to evaluate the expected effect from the use of renewable resources.…”
Section: Resultsmentioning
confidence: 99%
“…An important condition for this is to find the law of distribution of random variables, the choice of a mathematical model with a minimum number of parameters, the empirical distribution of the test characteristic in satisfactory certain physical and geographical conditions and within the required accuracy. Modeling the regime of geophysical processes makes it possible to determine the variability of the energy properties of solar radiation or water flow, the integral distribution function and the integral provision of the initial value [18]. It is necessary for further research to fully ensure the intensity of research characteristics, to evaluate the expected effect from the use of renewable resources.…”
Section: Resultsmentioning
confidence: 99%
“…Examining the RMSE values stratified by season (Figures 14 and 15), winter and spring exhibit the worst performances for solar and wind power respectively, with the AnEn + DIcast generally still slightly overperforming compared to DICast alone. The performance is highly dependent on the season for solar power because of the climatology of Kuwait, with very frequent, easily predictable, clear sky conditions during the summer [43]. For wind power, there is an enhanced daily cycle in the RMSE in the summer with higher values during the night than during the day.…”
Section: Anen Resultsmentioning
confidence: 99%
“…where M @ is the clearness index. An hourly clearness index derived for Kuwait from a local data represented by mixture distributions model is used in this study [Tye, R., et al, 2019].…”
Section: Global Horizontal Irradiance Modelsmentioning
confidence: 99%
“…According to the latest financial statistics in Kuwait, it was found that there was an average interest rate of 3 %, while inflation was 2 % based on the increase in the consumer price index between the two financial years (2018-2019) [Central Bank of Kuwait, 2019. Thus, to calculate the LCCA from equation ( 27), the operations and maintenance cost is multiplied by the uniform present value factor (UPV) because it is expected to escalate in the future because of the rise in workers' wages and other elements included in the annual O&M costs.…”
Section: Overview Economic Analysis Lifecycle Cost Analysis (Lcca)mentioning
confidence: 99%